Fostering Adaptive Employees: The Importance of Continuous Feedback in HR Development - Warin, Araya Kanchanapisek; Darmawan, Didit (Metromedia, 2024)
This research aims to examine the implementation strategies and organizational impact of continuous feedback systems as a critical component of HR development. Continuous feedback serves as a catalyst for employee growth and organizational success. This approach encourages a culture of open communication, allowing employees to receive real-time insights that enhance their performance and professional development. Key benefits of continuous feedback include employee empowerment, immediate performance adjustments, strengthened employee-manager relationships, and overall development. To implement continuous feedback, organizations need to establish a clear framework, conduct regular checks, and provide training for managers on effective feedback techniques. In conclusion, continuous feedback is essential for improving employee engagement, performance, and retention. By prioritizing this practice, organizations can create a work culture that supports individual and collective success.